The Effectiveness of Interactive Video Tutorials in Enhancing Students’ Procedural Text Mastery Based on the Cognitive Multimedia Learning Theory - Emi Normanda; Prima Vidya Asteria; Trinil Dwi Turistiani (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
This study addresses the low level of procedural text mastery among junior high school students, as evidenced by 67% of eighth-grade students at SMP Negeri 2 Sampang failing to achieve the Minimum Mastery Criterion (MMC = 75). This situation highlights the need for more effective digital learning media to support Indonesian language instruction. The study aimed to develop and evaluate the effectiveness of interactive video tutorials based on the Cognitive Theory of Multimedia Learning (CTML) in improving students’ procedural text mastery. The research employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) using a mixed-methods approach. A total of 240 eighth-grade students participated in the study. Data were collected through expert validation, learning achievement tests, and student perception surveys. The results indicated that the developed media was categorized as “Very Good” based on expert evaluations. A paired-samples t-test revealed a significant improvement in student learning outcomes (t = 15.47, p < 0.001), with mean scores increasing from 65 to 82. Cohen’s d value of 1.42 indicated a large practical effect. The percentage of students achieving mastery increased from 33% to 87%, exceeding the predetermined target. In addition, students expressed highly positive perceptions of the interactive video tutorials. These findings suggest that CTML-based interactive video tutorials effectively enhance procedural text mastery and can serve as an innovative instructional medium that supports the digital transformation of Indonesian language learning at the junior high school level.   Penelitian ini dilatarbelakangi oleh rendahnya penguasaan teks prosedur siswa SMP, yang ditunjukkan oleh 67% siswa kelas VIII SMP Negeri 2 Sampang belum mencapai Kriteria Ketuntasan Minimal (KKM = 75). Kondisi tersebut menunjukkan perlunya media pembelajaran yang lebih efektif untuk mendukung pembelajaran bahasa Indonesia. Penelitian ini bertujuan mengembangkan dan mengevaluasi efektivitas tutorial video interaktif berbasis Cognitive Theory of Multimedia Learning (CTML) dalam meningkatkan penguasaan teks prosedur siswa. Penelitian menggunakan model ADDIE (Analysis, Design, Development, Implementation, Evaluation) dengan pendekatan mixed methods. Sebanyak 240 siswa kelas VIII dilibatkan sebagai subjek penelitian. Data diperoleh melalui validasi ahli, tes hasil belajar, dan survei respons siswa. Hasil penelitian menunjukkan bahwa media yang dikembangkan memperoleh kategori “Sangat Baik” berdasarkan penilaian ahli. Uji paired t-test menunjukkan peningkatan hasil belajar yang signifikan (t = 15,47; p < 0,001), dengan rata-rata nilai meningkat dari 65 menjadi 82. Nilai Cohen’s d sebesar 1,42 menunjukkan pengaruh praktis yang besar. Persentase ketuntasan belajar meningkat dari 33% menjadi 87%, melampaui target yang ditetapkan. Selain itu, sebagian besar siswa memberikan respons positif terhadap penggunaan video interaktif dalam pembelajaran. Temuan ini menunjukkan bahwa tutorial video interaktif berbasis CTML efektif meningkatkan penguasaan teks prosedur dan berpotensi menjadi alternatif media pembelajaran yang mendukung transformasi digital pendidikan bahasa Indonesia di tingkat sekolah menengah pertama.